The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s00251-015-0869-7
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of natural killer cell receptors

Abstract: Natural killer (NK) cells are immune cells that play a crucial role against viral infections and tumors. To be tolerant against healthy tissue and simultaneously attack infected cells, the activity of NK cells is tightly regulated by a sophisticated array of germline-encoded activating and inhibiting receptors. The best characterized mechanism of NK cell activation is “missing self” detection, i.e., the recognition of virally infected or transformed cells that reduce their MHC expression to evade cytotoxic T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 156 publications
0
67
0
1
Order By: Relevance
“…This is evident from the KIR gene family, which is tightly clustered and shows variations in gene copy numbers for different human haplotypes in addition to sequence diversity in the population based on 15 to 112 alleles for different loci [9]. Variations in the KIR region is thought to result from genomic instability driven by shared sequences within and surrounding the genes, including minisatellite sequences in the first intron, all of which can lead to crossing over among the tandemly arranged genes, expansion and contraction of gene numbers from meiotic mispairing, in addition to recombination, gene conversion, domain shuffling, duplications and deletions and single nucleotide polymorphisms ([45, 46], reviewed in [47, 48]). Similar to the assembly problems for the Sp185/333 gene family, the attributes of the KIR family have also resulted in very poor assembly in macaque genome sequences [49].…”
Section: Discussionmentioning
confidence: 99%
“…This is evident from the KIR gene family, which is tightly clustered and shows variations in gene copy numbers for different human haplotypes in addition to sequence diversity in the population based on 15 to 112 alleles for different loci [9]. Variations in the KIR region is thought to result from genomic instability driven by shared sequences within and surrounding the genes, including minisatellite sequences in the first intron, all of which can lead to crossing over among the tandemly arranged genes, expansion and contraction of gene numbers from meiotic mispairing, in addition to recombination, gene conversion, domain shuffling, duplications and deletions and single nucleotide polymorphisms ([45, 46], reviewed in [47, 48]). Similar to the assembly problems for the Sp185/333 gene family, the attributes of the KIR family have also resulted in very poor assembly in macaque genome sequences [49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CD8 + T lymphocytes, natural killer (NK) cells have a crucial role in the recognition and killing of virus-infected/tumor cells, but unlike CD8 + T-cells, they use a repertoire of germ-line encoded inhibitory/activating receptors that recognize “missing self”/“altered-self” antigens on the target cells leading to cytotoxicity and cytokine production (3). These NK cell receptors (NKRs) are also expressed on certain subsets of T-cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that infection of various mouse and rat cells with a number of viruses (MCMV, RC-MV-E, vaccinia, ectromelia) promotes a rapid loss of mouse Clr-b ( Clec2d ) and the rat Clr-b homolog rClr-11 ( Clec2d11 ) at both the steady-state transcript and cell surface levels [6,16,18,19] . To distinguish between infected and uninfected (bystander) cells at the single cell level, we infected mouse NIH3T3 fibroblasts over an early time course using a modified MCMV-GFP reporter virus in which an enhanced GFP transgene is driven by an immediate early gene (ie1/3) promoter in the MCMV-Smith (VR-194) strain [19][20][21] .…”
Section: Infection Reciprocally Modulates Clr-b Levels On Infectmentioning
confidence: 99%
“…All of these receptors are encoded within the NK gene complex (NKC) located on mouse chromosome 6, rat chromosome 4, and human chromosome 12 [5] , yet a number of loci encoding other NKR, including NKp46 ( Ncr1 ) and 2B4 ( Cd244 ), are located outside the NKC [reviewed in 6 ].…”
mentioning
confidence: 99%